CUSTOMER SATISFACTION INDEX WITH A QUALITY OF SERVICE IN PUBLIC MASS TRANSPORT - Poliakova, Adela (Doprava a spoje, 2010)
The submission deals to problem of customer satisfaction value determination in the area of public mass transport. The first part of this paper is devoted to a description of the difference between consumer understanding of quality and own customer enjoyment. The passenger satisfaction is possible to consider in the case of high standard of service. The core contribution is an analysis approach for determining the value of customer satisfaction index in the application area for mass transport. Using the customer satisfaction index is gradually improving its objective by reducing the difference between expectations and perceptions of product characteristics.